The studying and synoptic analysis of mechanical in mechanism of widespread winter precipitation of Iran - masoud jalali; mehdi doustkamian; amin shiri karim vandi (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study was to analyze the mechanism is precipitation Comprehensive Iran. For this purpose the daily precipitation data of 483 synoptic and climatology stations arranged. In this study, a comprehensive annual rainfall is said to have a minimum rainfall and above, 50% sequence coverage and have at least two days. Winter surround Iran on the condition of rainy days were extracted and examined. Then, to review and analyze the mechanism of atmospheric precipitation comprehensive synoptic and dynamic parameters such as moisture flux, vortices, ground level pressure, Geopotential, meridional and zonal wind component for the levels of 1000, 850, 700 and 500 HP studied and analyzed was. The results of this study showed that the widespread mechanism of dynamic and synoptic Winter country most affected by the composition of the atmosphere patterns such as the Mediterranean low pressure - low pressure core Persian Gulf, Iran, Central High East Europe closed low pressure, low pressure Urals - the Middle East, high pressure, low pressure Saudi Arabia - High pressure belt Europe and Siberia - Iran's low-pressure center. However most of the winter precipitation of moisture flux feed barley middle-Level interaction, particularly levels of 850 and 700 HP respectively. It was while change 500 hPa atmospheric dynamical mechanism is an important role in Iran's winter inclusive.